University Calculus: Early Transcendentals (3rd Edition)

Published by Pearson
ISBN 10: 0321999584
ISBN 13: 978-0-32199-958-0

Chapter 3 - Section 3.3 - Differentiation Rules - Exercises: 10

Answer

$y'= -2+3x^{-4} $ $y'' = -12x^{-5}$

Work Step by Step

$y= 4 - 2x - x^{-3}$ $y'= 0-2+3x^{-4} $ $y'= -2+3x^{-4} $ $y'' = 0-12x^{-5}$ $y'' = -12x^{-5}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.